Salivary gland enlargement and sialorrhoea in dogs with spirocercosis: A retrospective and prospective study of 298 cases - Liesel L. van der Merwe (Journal of the South African Veterinary Association, 2012)
This longitudinal cross-sectional clinical study investigated the incidence of sialorrhoea in dogs with spirocercosis and determined whether breed, body weight and the extent of the oesophageal involvement was associated with this presentation. A retrospective analysis was performed on the medical records of 233 dogs and information pertaining to 65 dogs was collected as part of a prospective study. All the animals were client-owned. Patients from the retrospective study underwent thoracic radiography or oesophageal endoscopy to diagnose and characterise the infection and were placed on therapy with a macrocyclic lactone, whereas the patients in the prospective study had both radiography and endoscopy routinely performed and biopsies of the oesophageal nodules collected where possible. Tru-cut biopsies of affected salivary glands were taken in 10 of 13 patients demonstrating clinical signs of sialorrhoea and salivary gland enlargement. The entire salivary gland was sectioned in an additional three dogs with spirocercosis and no sialorrhoea that were presented for post mortem examination. Sialorrhoea was present in 33/298 cases (11%). Fox terrier breeds were over-represented in the patients with sialorrhoea, comprising 36% of cases, whereas they only comprised 1.5% of the patients without sialorrhoea (p < 0.001, chi squared test) and 5% of the combined group. Dogs weighing 12 kg or less were significantly over-represented in the sialorrhoea group, 69% versus 19.5% (p < 0.001, chi square test). Age was not significantly different between the two groups (p < 0.08, Mann-Whitney test). The number of oesophageal nodules per case was significantly higher in the non-sialorrhoea cases (p = 0.048, Mann-Whitney test). The prevalence of distal oesophageal and lower oesophageal sphincter involvement, and neoplastic transformation of the nodules were not statistically different between the two groups. None of the fox terriers in either group showed neoplastic transformation of the parasitic nodules even though they were over-represented as a breed. Mandibular salivary glands were affected in 86% of cases showing sialorrhoea. Histopathology revealed acinar hyperplasia in all cases with concurrent necrosis detected in only two cases. Sialorrhoea and salivary gland enlargement has an incidence of 11% (33/298 cases) in canine spirocercosis. Small breeds (≤ 12 kg) and particularly fox terrier breeds are over-represented in the group demonstrating sialorrhoea and this appeared to be the only risk factor. The conclusion was that sialorrhoea secondary to canine spirocercosis occurs frequently and its presence should prompt further investigation for oesophageal and gastro-intestinal disease. Severely affected patients can be managed with phenobarbitone to control the dysphagia in addition to the routine macrocyclic lactones treatment.